Salmonella paratyphi-induced splenic vein thrombosis: A case report on infrequent cause of acute abdomen - Ruchika Saini (Wolters Kluwer Medknow Publications, 2021)
Splenic vein thrombosis and splenic infarction are complications beyond the usual clinical spectrum of paratyphoid fever, and the presentation is rarely described. We report the case of a young female, who presented with high-grade fever and severe left upper quadrant pain. Her blood culture was positive for Salmonella paratyphi A, with Widal test suggesting 4-fold rise in titers. Computed tomography revealed splenic vein thrombosis and multiple splenic infarcts, for which antibiotic and anticoagulation were instituted simultaneously. She had a complete resolution with this management, and anticoagulation was tapered off on subsequent visits.